2014
DOI: 10.1039/c4nr00974f
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-selective promoter recognition accompanies antitumor effect by glucocorticoid receptor-targeted gold nanoparticle

Abstract: Nanoparticles, such as gold nanoparticles (GNP), upon convenient modifications perform multi tasks catering to many biomedical applications. However, GNP or any other type of nanoparticles is yet to achieve the feat of intracellular regulation of endogenous genes of choice such as through manipulation of a gene-promoter in a chromosome. As for gene modulation and delivery, GNP (or other nanoparticles) showed only limited gene therapy potential, which relied on the delivery of 'exogenous' genes invoking gene kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Dynamic light scattering data showed that the average size (Z av ) of AuNPs and AuNPs‐Qu‐5 were 10.58 and 15.92 nm, respectively (Figure A,B). The comparatively large size of AuNPs‐Qu‐5 was observed in DLS indicated the attachment of the drug on gold nanoparticles surface . The size of AuNPs and AuNPs‐Qu‐5 acquired from DLS was slightly higher than that obtained from TEM.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Dynamic light scattering data showed that the average size (Z av ) of AuNPs and AuNPs‐Qu‐5 were 10.58 and 15.92 nm, respectively (Figure A,B). The comparatively large size of AuNPs‐Qu‐5 was observed in DLS indicated the attachment of the drug on gold nanoparticles surface . The size of AuNPs and AuNPs‐Qu‐5 acquired from DLS was slightly higher than that obtained from TEM.…”
Section: Resultsmentioning
confidence: 87%
“…The wavelength at maximum absorbance of AuNPs‐Qu‐5 showed considerable shift (λmax ~540 nm) from the naked AuNPs (λmax ~530 nm), indicating feasible attachment of the drug molecule on AuNPs surfaces (Figure A) . This result indicates the alteration of photo‐physical properties of AuNPs by the physical association of Qu, on gold nanoparticle surfaces …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The membrane was again washed with TBS‐T and incubated with secondary antibody for 1 h at dark at room temperature. Finally, after washing the secondary antibody, blots were developed by colorimetric method using NBT/BCIP developing solution …”
Section: Methodsmentioning
confidence: 99%